Development of a cognitive-based smartphone application for Malaysian Parkinson’s disease patients: exploring the possibility? - Mohamed, Wael Mohamed Yousef; Koya Kutty, Shahedah; Khedher, Akram M Z M; Chatterjee, Indranath (Neurotak Publishing, 2022)
The COVID-19 pandemic has accelerated the digital health system. Healthcare organizations want to give medical treatment to individuals who live a great distance away. As a result, they are emphasizing the creation of bespoke telemedicine apps. The number of individuals using telemedicine apps is increasing significantly. Increasing technology gives patients healthcare resources. This has been made feasible via a new telemedicine system and by developing a telemedicine app. Patients can use several technologies to communicate with healthcare professionals. For comfort and privacy, you can employ live visual media. The creation of telemedicine apps is the most attractive and practical investment. With the growing availability and usage of technology in PD, the focus of these technologies is gradually turning toward the disease's vast spectrum of Non-Motor Symptoms (NMS). The nature of NMS makes them difficult to objectively measure, further development and building on experience gained in other conditions may still result in NMS capture that is feasible. Although it is impossible to offer recommendations for the use of digital technology outcomes for NMS in clinical practise based on currently available data, evidence for these devices is evolving, and such guidance may become accessible in the not-too-distant future. To our knowledge, this is the first telemedicine method of its sort to address cognition as one of the NMS in Malay PD patients. The project will be done on two consecutive phases (1 year each); Phase1 aims to develop the Dementia Coach Mobile App, and Phase2 aims to validation of this app by using PD patients sample from SASMEC. Therefore, we hypothesize that developing a friendly mobile app to assess dementia for PD patients is highly beneficial and could be used for diagnosis of NMS in PD patients.